Characterisation of quorum sensing and antibiotic resistance genes from the genomes of selected cultivable oral bacterial isolates / Goh Share Yuan - Goh , Share Yuan (2018)
Oral cavity is the primary gateway to the human body. It is the desired habitat for microorganism proliferation due to its optimum condition. Oral microorganisms are capable of passing through the circulatory system and spread to different human anatomy. Root caries refers as a significant oral health problem. Dentinal caries occurs at dentine layer which is caused by a supra-gingival microbial biofilm. Whole genome sequencing coupling with systematic bioinformatics analysis offers unprecedented insights into important genomic features and characteristics of genes including those putative quorum sensing genes and profiling of antimicrobial resistance. Quorum sensing is a type of cell-cell communication to control the expression of genes linked to cell density. It could serve as a basis for non-antibiotic based drug discovery to attenuate pathogenic bacterial population by controlling bacterial quorum sensing. Understanding the profile of antibiotic resistance genes is essential to predict antibiotic resistance in oral bacteria and this provides invaluable information for clinical use especially prescription of drugs. The objectives of this study were to analyse the genome sequences of culturable oral bacteria from dental caries, identify the presence of quorum sensing genes as well as to characterise their antimicrobial resistance genes. This work utilised high-resolution technologies such as triple quadrupole liquid chromatography-tandem mass spectrometry for the detection of quorum sensing molecules, MALDI-TOF mass spectrometry for bacterial identification and next generation sequencing on MiSeq platform coupling with numerous bioinformatics resources to understand the genome biology of these isolates. Based on the diverse morphologies of oral microbial, a total of 21 cultivable strains were isolated and identified, namely Burkholderia cepacia, Citrobacter amalonaticus, Elizabethkingia sp., Enterobacter spp., Klebsiella spp., Pseudomonas aeruginosa, Pluralibacter gergoviae, Lacobacillus paracasei, Strenotrophomonas maltophilia, Citrobacter koseri and Proteus mirabilis. Among these strains, some are uncommon to oral bacteria community that exhibited quorum sensing namely Citrobacter amalonaticus and Enterobacter spp. To the best of my knowledge, this is the first work of its kind that reports the quorum sensing activity by Citrobacter amalonaticus.